Pengaruh Kepuasan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan pada Salon Kecantikan RC’L Aesthetic Karawang - Selvi Ilalia; Budi Rismayadi; Wike Pertiwi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to analyze the influence of job satisfaction and work discipline on employee performance at the RC'L Aesthetic Karawang Beauty Salon. The research method used is quantitative with saturated techniques (Total Sampling), with a population of 45 employees. Data were collected using a questionnaire and analyzed using the multiple linear regression method. These results indicate that job satisfaction has a significant positive influence on employee performance, with a regression coefficient value of 0.109 and a significance value of 0.036. Work discipline also has a significant effect on employee performance with a regression value of 0.487 and a significance value of 0.001. Simultaneously, these two variables contribute 39.7% to the variation in employee performance. This research emphasizes the importance of managing job satisfaction and integrated work discipline to increase productivity and service quality. This research can be a reference for management in increasing employee job satisfaction and strengthening and strengthening a culture of discipline, balance between work and employee personal relationships in order to achieve optimal performance.